Erythrocute and leukocyte counts in different goat breeds before and after anthelmintic treatments - Costa, Carlos Alberto Fagonde; Pant, Kant Prasad (Pesquisa Agropecuaria Brasileira, 2014)
Erythrocyte, total leukocyte and eosinophil counts, just before and 14 or 17 days after anthelmintic treatments given in two seasons, were determined in kid goats of five breeds. The erythrocyte counts were affected (P<0.005) by the goat breeds and by the anthelmintic treatments. Considering that the animals were kept in pasture contaminated by Haemonchus sp., it is presumed that goats with the lowest erythrocyte counts (Bhuj in rainy and Marota in dry season) were the most infected. Similarly, it is presumed that goats with the highest counts before treatments (Anglo-Nubian and Moxoto in rainy and dry, and Caninde in dry season) were the least infected. The Caninde were the only goats whose erythrocyte counts were not further increased by anthelmintic treatment in any season. Maximum eosinophil percentages were observed in Caninde and Anglo-Nubian goats before anthelmintic treatment in dry season. At this time, the eosinophil percentages were reduced by the treatment. Considering that eosinophilia follows inflammatory and immune reactions against helminth parasites, it is possible that high eosinophil percentages in Caninde and Anglo-Nubian breeds indicate a efficient defence system. Accumulation of more data is necessary to reach final conclusions.